ECOLOGICAL MODEL: A THEORETICAL PROPOSAL TO UNDERSTAND RISK AND PROTECTION FACTORS FOR VIOLENCE AGAINST WOMEN - de Mello, Isabelle Poli Bandeira; Zamora, Maria Helena Rodrigues Navas (Seven Editora, 2025)
Studying intimate partner violence against women is essential; it is defined by the WHO as a public health problem. To illustrate the seriousness of the issue, some data on violence against women (VAW) in Brazil are presented. The article aims to understand the preventive factors (risk and protection) that involve VAW aiming at the prevention of violence, through a theoretical review, exploring concepts pertinent to the theme such as diversity, intersectionality, risk and protection factors. Heise's ecological model is proposed as an essential theoretical resource to guide the understanding of VAW and the care of these women. Understanding the factors related to VAW perpetrated by intimate partners can make interventions more efficient, aiming to contribute to the construction of public policies and interventions that can contribute to the end of this reality that plagues millions of women not only in Brazil but also in the world.DOI: https://doi.org/10.56238/sevened2025.018-019